KIAI'S PARTICIPATORY LEADERSHIP MODEL IN DELEGATING TASKS IN ISLAMIC BOARDING SCHOOL: BETWEEN TRADITION AND DISRUPTION - Savira, Himma; Naufal, Muhammad Bahy; Anwar, Moh. (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Study This is motivated by the challenges Islamic boarding schools face in Indonesia due to the disruption of technology and globalization.  Pondok Islamic boarding school Diponegoro Klungkung Bali becomes the main focus of the study.  This is Because the leadership of Kiai at the Islamic boarding school must be capable of balancing preservation values and traditions with the demands of modernity.  Research reveals How leadership can respond to disruption without ignoring existing traditions.  Research This uses an approach that includes a design study case.  Data was collected through interviews with Kiai, administrator foundations, and teachers and direct observation of activities in Islamic boarding schools.  Analysis was done using descriptive and interpretive methods to identify patterns of leadership participation and the challenges faced.  Research results show that participatory leadership in Kiai involves deliberation, open, and delegated practical tasks capable of balancing tradition and innovation.  However, challenges exist, especially concerning source power, human resources, and material limitations.  Research This gives an essential outlook on relevant leadership strategies in the era of disruption.